Kiút a szegénységből. a Kiútprogram Közhasznú Non-Profit Zrt. bemutatása és finanszírozása - Knoll, Gabriella (Acta Scientiarum Socialium, 2013)
A way out of poverty. Presentation of the Kiútprogram Közhasznú Nonprofit cPlc. and its financing My article summarizes and compares the concept of Grameen Bank (Bank of Poor’s) and the implemented program in Hungary, Kiútprogram Közhasznú Nonprofit Zrt. (cPlc.). I examine the success of the program in a country (Hungary) where a functional social system is already set up.
Keywords: poverty; loan; no coverage; bank; social system